THE DEVELOPMENT OF VII GRADE LESSON PLAN FOR SCIENCE SUBJECT WITH 3N: NITENI, NIROKNE, NAMBAHI (TO INQUIRE, TO COPY, TO ADD) TAMANSISWA APPROACH WITH OUTDOOR LEARNING ACTIVITY BASIS - Wijayanti, Astuti; Utaminingsih, Retno (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
Learning process with 3N Tamansiswa approach (Niteni (inquire), Nirokke (copy), Nambahi (add/innovate)) which is based on outdoor learning is an innovative learning inviting the student to think creatively and develop their processing skills in learning. This 3N approach is in line with the scientific approach in 2013 curriculum. The development of Integrated Science Lesson Plan for VII grade students based on 3N Tamansiswa and Outdoor Learning Activity was done to know that the lesson plan is proper to be used to teach integrated science for VII grade students. This research used R&D method from Sukmadinata, that it involves: 1) initial study which includes literature study and the proposal for initial draft of the product, 2) the development of integrated science lesson plan for VII grade of Junior High School students with 3N Tamansiswa approach and Outdoor Learning Activity, and 3) the evaluation with limited trials and wider trials. The data were collected by Focus Group Discussion (FGD), documentation, and distribution of the questionnaire. The result showed that the lesson plan of Science Subject for VII graders with 3N Tamansiswa and Outdoor Learning Activity approaches was proper for teaching science. The quality of the lesson plan was scored averagely in 91 in the good category by reviewers in FGD I. The score was increased to 99 in FGD II in a good category.